The effects of the Dutch disease in Russia - Bernardina Algieri (University of Bonn, Center for Development Research (ZEF), 2004)
This paper shows how the Dutch Disease has affected the Russian economy since the start of the transition in the early 1990s. Four symptoms have been detected, namely: 1) a real exchange rate appreciation, 2) a temporary improved economic situation, 3) an output decline in the non-booming-sector, 4) an export reduction in the non-booming-sector. An extended version of the Balassa-Samuelson model has been implemented to test symptom 1. Our results suggest a positive long-run cointegration relationship between the real exchange rate and the oil price. A 7% real appreciation is caused by a 10% oil price shock. Moreover, a 10% increase in oil prices leads to a 2% GDP growth, while a 10% real appreciation is associated with a 2.1% output decline. The total effect on GDP growth, considering the Balassa-Samuelson effect, confirms symptom 2. Finally, the domestic industrial production drops and high-tech and textile exports are crowed out. This indicates that the Russian economy is also affected by symptoms 3 and 4. We conclude that Russia's government should invest the tax revenues collected from the resource sector such that the structure of the economy becomes more diversified and less vulnerable to exogenous shocks.
Keywords: 330; Political Economy; Rohstoffreichtum; Ölpreis; Schätzung; Russland; Balassa-Samuelson Effekt